Phenotypic performance and response to selection for reproductive traits of black bengal Goat (BBG) in a community breeding program (Bangladesh Journal of Agriculture, 2022)
Black Bengal Goat (BBG) is only one goat breed in Bangladesh popularly known for its’ fecundity and carcass quality. The study aimed to investigate the genetic improvement of this goat breed in-situ through a community-based breeding program under a low input production system in three villages namely Gangatia, Borochala, and Pachpai in Bhaluka upazila of Mymensingh district. Data on a total of 657 individuals included with three progressive generations taken during 2009 - 2015 were analyzed for performance evaluation and genetic improvement as a result of two breeding strategies (BS) viz. mating within superior bucks and does, and within superior bucks and existing does and also compared with a control group mated among existing bucks and does. Statistical analysis was performed by SPSS 17.0 and genetic parameters by VCE 4.2.5. The average age at sexual maturity (ASM), age at first kidding (AFK), services per conception (SPC), litter size (LS), postpartum heat period (PPHP), and kidding interval (KI) were 233.09±2.71d, 383.01±2.61d, 1.13±0.03, 1.90±0.05, 42.41±0.84d and 186.44±0.95d, respectively. Generation and BS had significant effect on all traits, except SPC, except AFK, all other traits differed significantly among the flocks. The heritability estimates of all reproductive traits were medium ranging from 0.32 to 0.57. Genetic and phenotypic correlations among reproductive traits were low to medium (-0.03 to 0.37). The overall responses of up to three generations for ASM, LS, PPHP, and KI were -15.59d, 0.12 no, -6.14d and -7.66d per generation, respectively. It is concluded that community based breeding program with selected superior bucks and does is very rationale under a low input production system, as it improves reproductive performance in progressive generations. However, estimates of heritability and genetic correlations indicate the scope of improvement for reproductive traits with selection and breeding among does and bucks with proven genetic worth.Bangladesh J. Agri. 2019-2021, 44-46: 97-113